PENGARUH INTERVENSI 20-20-20 RULE TERHADAP PENURUNAN GEJALA COMPUTER VISION SYNDROME PADA MAHASISWA KEDOKTERAN SELAMA PANDEMI COVID-19 - Saniyyah Alyaa (2022)
Computer Vision Syndrome (CVS) are some of the problems that arise in the eyes due to using computers, tablets, and smartphones for a long time. Since there has been a worldwide pandemic, online activities are considered to be an alternative to carrying out daily activities and cause the incidence of CVS to increase. This study aims to determine the effect of the 20-20-20 rule intervention on the severity of CVS in medical students during the COVID-19 pandemic. This study is a quasi-experimental study using a one-group pretest-posttest design. The sample size of 75 people was taken using the proportional stratified random sampling technique. The research instrument used a Computer Vision Syndrome Questionnaire (CVS-Q), Eye Care-Protect Your Vision application, desk time, and screen time. The results of the analysis of the total screen time of smartphone use were obtained for 8 (3-12) hours, laptops for 10 (6-19) hours, and television for 2 (1-11) hours. The results of the analysis using the Wilcoxon test showed that the 20-20-20 rule intervention could reduce all CVS symptoms (p ≤ 0.001). The results of the Wilcoxon test showed that the CVS symptom score after the intervention was lower in 73 people and 2 people the score was fixed (p = 0.000). It can be concluded that the CVS symptom score was significantly reduced after the subject intervened with the 20-20-20 rule. This can occur because the relaxation process that takes place during rest can cause a decrease in symptoms